Direct Synthesis of Metal‐Doped Phosphorene with Enhanced Electrocatalytic Hydrogen Evolution. Issue 7 (10th April 2019) - Liu, Danni; Wang, Jiahong; Lu, Jiang; Ma, Chao; Huang, Hao; Wang, Zhongzheng; Wu, Lie; Liu, Qian; Jin, Shaowei; Chu, Paul K.; Yu, Xue‐Feng
Abstract: 2D materials with large specific surface area and robust mechanical properties are appropriate for electrocatalysis. However, the unsatisfactory adsorption energy and limited active sites restrict their commercial application. Herein, a facile and rapid electrochemical strategy enabling synchronous exfoliation and doping is designed to directly synthesize metal‐doped 2D materials from the bulk crystals. By using black phosphorus as a model, various metal doped phosphorene such as BP(Co), BP(Mo), and BP(Ni) is obtained, and a synergistic synthesis mechanism is proposed. Notably, the dopant introduces electronic band transformation, charge redistribution, and state occupation confirmed by density functional theory calculations. Owing to the enhanced electro‐conductivity, abundant metal‐P active sites, and optimized adsorption energy by doping, the BP(metal) exhibits enhanced hydrogen evolution reaction activities and stability in comparison to the bare phosphorene. Particularly, BP(Co) presents highest activity with a potential of 0.294 V at 10 mA cm −2 (the current density is normalized with electrochemical surface area by using a double‐layer capacitance method). This study provides new access to synthesize highly efficient electrocatalysts, and also enriches the structure modulation means for layered 2D materials. Abstract : Metal doped phosphorene is developed by a facile and rapid electrochemical method from bulk black phosphorus. This method enables synchronous exfoliation and transition metal doping based on the synergistic effect among intercalator molecular, metal ions, and the solvent. The metal‐doped phosphorene delivers much improved electrocatalytic performance than bare phosphorene.